2008
DOI: 10.17221/417-pse
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of nematodes in wetland soils with difference distance from the Bohai sea 359-366

Abstract: In order to elucidate the distribution of soil nematodes in coastal wetlands and the effect of different distance from the sea line on soil nematode communities, we investigated the community structure of soil nematodes in one wetland perpendicularly oriented from Bohai sea coastline. In June 2006, soil samples were collected from the Yellow River Delta wetlands, in Dongying city of Shandong Province, China. Soil nematode communities were analyzed at the depths of 0-10 and 10-20 cm. The results showed that pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The data obtained in the present study indicated that wetland reclamation had significant effects on the abundance of plant-feeding nematodes, the proportions of plant-feeding nematodes were GW (91.0%) > TW (88.1%) > CW (53.5%) ( Table 2). Similar results were found by Wu et al (2008) who observed the plant parasite nematodes were the most abundant trophic groups in wetland soils, and the average relative abundance was 91.33% of the nematode community. Plant parasite and omnivore-predator nematodes were more sensitive to the ecophysiological individual features of observed plants versus the total number of nematodes and bateriaand fungi-feeding nematodes (Stanislav et al, 2008), which can explain the changes of soil nematode communities composition in the different types of wetland soils.…”
Section: Effects Of Wetland Reclamation On Functional Guildssupporting
confidence: 89%
“…The data obtained in the present study indicated that wetland reclamation had significant effects on the abundance of plant-feeding nematodes, the proportions of plant-feeding nematodes were GW (91.0%) > TW (88.1%) > CW (53.5%) ( Table 2). Similar results were found by Wu et al (2008) who observed the plant parasite nematodes were the most abundant trophic groups in wetland soils, and the average relative abundance was 91.33% of the nematode community. Plant parasite and omnivore-predator nematodes were more sensitive to the ecophysiological individual features of observed plants versus the total number of nematodes and bateriaand fungi-feeding nematodes (Stanislav et al, 2008), which can explain the changes of soil nematode communities composition in the different types of wetland soils.…”
Section: Effects Of Wetland Reclamation On Functional Guildssupporting
confidence: 89%
“…The study revealed the presence of trophic groups comprising of herbivores, fungivores, bacteriovores and omnivores-predaceous. The distribution of nematodes in the agro-ecosystem was similar to the nematodes reported by Wu et al, (2008) and Lawal and Atungwu (2012). Application of organic amendment of composted plant materials stacked on poultry dung on eggplant field led to the development of a complex ecosystem which was found to be constituted by varying population of nematode species each with different feeding characteristics.…”
Section: Discussionsupporting
confidence: 78%
“…Preferential by the innate characteristics gifted to all living creatures by nature; they also have the ability to carry out all physical and physiological processes such as reproduction, feeding, excretion, response to stimuli as well as movement from place to place. Spatial and temporal distribution of nematodes in aquatic and terrestrial ecosystem has been well studied (Wu et al, 2008;Atungwu, 2013 andNzeako et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peatlands are ecosystems that are created on locations permanently waterlogged by precipitation, surface, or underground water. Understanding the hydrological system is crucial for sustainable land development, and effective soil and nature conservation and site hydrology appear as the main force of secondary succession [ 5 , 6 , 7 ]. In conditions of reduced air, organic residues in various stages of decomposition are accumulated, and peatland is created.…”
Section: Introductionmentioning
confidence: 99%